Characterization Of Lignocellulosic Film Made Of Unbleached Pulp Solutions And Cellulose Nanowhisker From Oil Palm Empty Fruit Bunch - Norazli, Najieha (2024)
Studies of bio-nanocomposites using sustainable green materials from biomass waste are presently gain the attention worldwide. Lignocellulosic biomass in the form of plant materials offers the most abundant renewable resource in replacing traditional fossil resources. In the present study, lignocellulosic biomass films were prepared directly from oil palm empty fruit bunch OPEFB pulp solutions in DMAc/LiCl without additional film-forming additives incorporated with 1%, 3%, and 5% via solvent casting method using various types of OPEFB CNW isolated using different types of delignification treatment and then casted into films. Mechanical behaviour, morphological properties, thermal properties, and functionality groups and the effect of adding the OPEFB CNW into the bio-nanocomposites films were then evaluated by infrared spectroscopy (FTIR), contact angle, mechanical analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric (TGA) and differential scanning calorimeter (DSC). The semi-transparent film with a yellowish colour was obtained due to the presence of lignin. The results showed good compatibility of lignocellulosic material and CNW which is responsible for the increasing in mechanical properties of the film. This also led to less hydrophilicity of the film as the filler loading increasing and no big difference between the effects of two types of CNW used. FTIR analysis spectra show a similar pattern with only different in the intense and broadening of the peaks.